The Role of Zakat in Support Sustainable Development Goals Achievement - Herman; Wahyudi; Fidela Dzatadini Wahyudi (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to analyze the strategic role of zakat in supporting the achievement of the Sustainable Development Goals (SDGs), identify the factors influencing its effectiveness, and develop an optimization model for zakat as an Islamic social finance instrument that promotes sustainable development and social welfare. Theoretical framework: The study is grounded in the principles of Islamic economics, Maqasid al-Shariah, and sustainable development theory. These perspectives explain how zakat functions as a mechanism for wealth redistribution, poverty alleviation, and equitable socio-economic development while advancing the objectives of human well-being and justice. Literature review: Previous studies have demonstrated that zakat contributes to poverty reduction, income redistribution, and social inclusion. However, existing research has largely examined these dimensions separately, with limited attention to integrating zakat, Maqasid al-Shariah, and the SDGs into a comprehensive conceptual framework for sustainable development. Methods: This research employed a qualitative approach using literature review and document analysis. Secondary data were collected from scholarly publications, reports of zakat institutions, government policy documents, and international reports related to Islamic social finance and sustainable development. The data were analyzed using thematic and interpretive techniques to identify patterns, relationships, and strategic implications. Results: The findings reveal that zakat significantly contributes to achieving SDGs by alleviating poverty, reducing socio-economic inequality, improving social welfare, supporting productive economic activities, enhancing food security, and expanding access to essential public services, including education, healthcare, and clean water. The effectiveness of zakat management is determined by institutional capacity, public literacy, governance quality, technological innovation, transparency, accountability, and collaboration among zakat institutions, governments, and other stakeholders. Implications: The study highlights the importance of strengthening zakat governance, digital innovation, and cross-sector collaboration to maximize the contribution of Islamic social finance toward inclusive and sustainable development aligned with the SDGs. Novelty: This study proposes an integrated conceptual model linking zakat, Maqasid al-Shariah, and the SDGs, providing a holistic framework for optimizing zakat as a sustainable Islamic social finance instrument that advances equitable socio-economic development.